Impact of Talent Management on Organizational Performance in Nepalese Non-government Organizations - Rijal, Rheet; Rijal, Chandra Prasad (KMC Journal, 2023)
This study opted for a positivist perspective-based deductive approach to determine the impact of talent management on organizational performance in Nepalese non-government organizations. The causal_comparative research design was used to determine the intensity and magnitude of the relationship between the selected constructs of the inquiry. To collect the primary data, an email survey was administered using referral sampling that generated a ‘sufficient’ sample size of 404 with complete responses by respondents of various demographic backgrounds. For the data analyses, descriptive and inferential analyses were used. The key findings of the study using the structural equation model revealed that attraction, selection, and retention were the drivers of improving organizational performance in the chosen context. However, talent development had no significant influence on organizational performance.